Synthetic Conditions and Color Characteristics of Tantalum Oxynitride Prepared via Liquid-NH3 Process. (22nd November 2009) - Sasaki, Yo; Tokuyasu, Zentaro; Ono, Yoichi; Iwasaki, Mitsunobu; Ito, Seishiro
Abstract : Tantalum oxynitrides, such as TaON, exhibit promising color properties and can be employed as nontoxic yellow pigments containing no heavy metals. We have developed a process for preparing nitrides or oxynitrides involving the vacuum-calcination of a precursor material obtained via reaction between a metal halide and liquidNH 3 . Herein, we describe the synthetic conditions of the liquid-NH 3 process that affect the color, and thus the color characteristics, of the resulting pigments. Reaction and postreaction treatment conditions were adjusted to obtain the desired yellow color. The liquid-NH 3 process was performed using 1.0 eq ofH 2 O (relative toTaCl 5 ) as the oxygen source and 30.0 eq of KCl (relative toTaCl 5 ) as flux. Calcination of the precursor at 1073 K under vacuum was followed by recalcination from room temperature to 973 K at rate of 10 Kmin − 1 under air. A powder with a color index ofL ∗ = 84.20, a ∗ = − 2.71, andb ∗ = 44.07 was obtained.